Penyuluhan Kesehatan Tentang Pentingnya Pemahaman Keluarga Tentang Kondisi Fisik Rumah Sehat Sebagai Upaya Pencegahan Infeksi Saluran Pernafasan Akut (Ispa) Pada Balita - Asmanidar; Asri Jumadewi; Fathimi, Fathimi; Hilma Yasni; Orisinal (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The causing ARI; host (smoking, ability of host to transmit infection, immunity, nutritional status, previous infection/concurrent infection with other pathogens, general health condition). Characteristics of the pathogen (mode of transmission, infectivity, virulence, number, dose, inoculum size). Environmental conditions (air pollutants, density of family members, temperature, humidity, cleanliness, ventilation, season). Availability of health services (vaccines, access to health services, capacity of isolation rooms). Humans are exposed to air pollution through eye contact and respiratory tract, particulates enter the body through breathing and settle in the lungs to the alveoli. Particulate impacts can occur directly or indirectly. Directly causes: eye, nose, throat irritation, headache, nausea, muscle aches, asthma and flu. After several years of exposure: decreased lung function, heart, lung cancer can be fatal. The importance of raising awareness and understanding of the community, especially those who have toddlers through health counseling efforts for the physical environment of the house.